Modeling of construction work combination during reconstruction - Romanushko, Ye.; Romanushko, V. (Ways to Improve Construction Efficiency, 2019)
The article deals with the modeling of combining construction works during reconstruction of buildings with the use of interchangeable work areas. The schedule for work combination with the representation of the placement of work areas within the object space and its timing is proposed. This allows to enhance the safety and efficiency of construction and installation works; decrease the time frame; and reduce the cost of reconstruction.